If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -7)(y + -9) = 0 Reorder the terms: (-7 + x)(y + -9) = 0 Reorder the terms: (-7 + x)(-9 + y) = 0 Multiply (-7 + x) * (-9 + y) (-7(-9 + y) + x(-9 + y)) = 0 ((-9 * -7 + y * -7) + x(-9 + y)) = 0 ((63 + -7y) + x(-9 + y)) = 0 (63 + -7y + (-9 * x + y * x)) = 0 (63 + -7y + (-9x + xy)) = 0 Reorder the terms: (63 + -9x + xy + -7y) = 0 (63 + -9x + xy + -7y) = 0 Solving 63 + -9x + xy + -7y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-63' to each side of the equation. 63 + -9x + xy + -63 + -7y = 0 + -63 Reorder the terms: 63 + -63 + -9x + xy + -7y = 0 + -63 Combine like terms: 63 + -63 = 0 0 + -9x + xy + -7y = 0 + -63 -9x + xy + -7y = 0 + -63 Combine like terms: 0 + -63 = -63 -9x + xy + -7y = -63 Add '7y' to each side of the equation. -9x + xy + -7y + 7y = -63 + 7y Combine like terms: -7y + 7y = 0 -9x + xy + 0 = -63 + 7y -9x + xy = -63 + 7y Reorder the terms: 63 + -9x + xy + -7y = -63 + 7y + 63 + -7y Reorder the terms: 63 + -9x + xy + -7y = -63 + 63 + 7y + -7y Combine like terms: -63 + 63 = 0 63 + -9x + xy + -7y = 0 + 7y + -7y 63 + -9x + xy + -7y = 7y + -7y Combine like terms: 7y + -7y = 0 63 + -9x + xy + -7y = 0 The solution to this equation could not be determined.
| 3/16x9 | | 232.74-9.50= | | 45x^4=20x^2 | | 8/15x=1/5 | | (x-5)(y+7)= | | y=6(3.5+1.5y)-11 | | 23*3.5= | | 169=a^2+144 | | 2x^2-10x-117=0 | | 2+3x=19+x | | c+1+c+2+c+3=189 | | 60(20)+20m=60m | | x+(2x+3)=15 | | y+7y+15y=29y+18 | | x+4x=500000 | | 27x^3+27x^2+9+1=0 | | (9u^2)/((u^2+u)^3) | | 8-8(x-4)=4 | | 6xy-2xy+8= | | 4x^3+12x^2+x+3= | | 12-4(a+2)=9+a | | (2u/3v^4)^3*(-4v^-3/8u^5)^-2 | | 7/(w+1)+3/(3w+3) | | -6(5r+5)+4r(4-5r)=1 | | y+21=56 | | 8/a+9-4/a+8 | | 6m+2m(m+7)=m-14 | | 3x+5y=269.50 | | x-.14(x)=223 | | 8-4/a+9(a+9) | | x+x+3x+35=180 | | x^2-4x-192=0 |